ANALISIS STRUKTUR ORGANISASI UNIT PERTOLONGAN KECELAKAAN PENERBANGAN DAN PEMADAM KEBAKARAN DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Regina Martenci Lea Korowa; Supri Supri; Agoes Soebagio (MANAJEMEN, 2025)
A clear and well-structured organizational system is a crucial factor in ensuring the effectiveness of emergency services at airports. This study aims to: (i) identify the organizational structure of the Airport Rescue and Firefighting (PKP-PK) Unit at Sultan Hasanuddin International Airport Makassar, (ii) assess its alignment with operational needs and emergency service standards, and (iii) evaluate personnel competencies in relation to national and international regulations. This research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation review regarding the structure and competencies of PKP-PK personnel. The findings indicate that the PKP-PK organizational structure at Sultan Hasanuddin International Airport formally complies with existing regulations, both in terms of hierarchy and functional division. Each position, from unit head to operational staff, carries clear roles in supporting emergency operations. Nevertheless, several challenges were identified, including the limited number of certified personnel, insufficient succession planning, uneven training implementation, delays in equipment procurement, and the lack of joint simulation exercises with stakeholders. The study concludes that although the organizational structure already meets operational requirements, the effectiveness of its implementation still requires strengthening personnel competencies, improving training quality, and enhancing cross-sector coordination to ensure optimal emergency services.